DETERMINATION OF PROCESSING PARAMETERS THAT MAXIMIZE THE PERFORMANCE AND STABILITY OF THE UNGURAHUI NECTAR (Oenocarpus bataua, C. Martius) - Fuentes Gómez, María Cecilia (2020)
The processing parameters that maximize the pulp yield and the stability of the ungurahui nectar were evaluated by means of the Taguchi and Response Surface methodologies. The raw material used came from the town of Yurimaguas, Loreto Region - Peru, and was subjected to weighing, selection, classification, washing, disinfecting, maturing, pulping, refining, filtering, standardized (to formulate the nectar), pasteurized, packed, cooled and stored processes. In the first stage the parameters of maturation and pulping were obtained (T°: 51,99 °C, time: 1,74 h, fruit harvested: water in maturation (1: 3), ripened fruit: water in the pulped (1: 0,75)), which optimized the yield (37,33%) of ungurahui pulp. In the second stage the standardized parameters were determined (pulp: water (1: 1,33), percentage of gums: xanthan (0,02 %), arabica (0,03 %), carboxymethylcellulose (0,06 %) and lecithin (0,02 %)) that optimized the stability (2,27 x10-8 ml (level of the ring on the surface of the bottle)) of the ungurahui nectar. The final product had a good acceptability of texture, taste and color. Likewise, low counts of viable mesophilic aerobes (10 CFU / ml), yeasts (<1 CFU / ml) and molds (<1 CFU / ml) ensured the quality of the product obtained.